Apinayé Indigenous Childhood: reflections on being a child in the village - Rosimar Locatelli; Janaina Ribeiro de Rezende (Revista Brasileira de Educação do Campo, 2023)
This article aims to reflect on socio-historical and cultural aspects of Apinayé childhood, based on a review of two ethnographic research carried out with this people, a TCC in Pedagogy, developed in 2012, and a Master's in Letters research, completed in 2016. We start from the understanding of childhood as a socio-historical construction. Therefore, when reflecting on the Apinayé children, we defend a sensitive and attentive approach to the ways of life of these people. We seek to consider cultural, ethnic, generational, historical and geographic aspects to try to understand this childhood. We emphasize that the Apinayé culture, experienced and practiced by children through rites, traditions and customs, occupies a constitutive dimension of childhood for this people. Furthermore, children not only reproduce what they are taught, but they invent, create and transform what is offered to them through peer culture, as active subjects who play, elaborate and build. The body, the relationship with nature and children's groups are essential to understand the way these children are in the world. More than bringing conclusions about the way of being an indigenous child, we propose reflections on possible childhoods, woven between games, responsibilities and learning in the Apinayé villages.